Penjadwalan Tenaga Kerja untuk Menentukan Regular Days Off (RDOs) dengan Menggunakan Algoritma Monroe - Khalida Syahputri; Jelly Leviza; T Keizerina Devi (Media Teknika, 2017)
ABC Company is a company producing rubber crumb (crumb rubber) in the form of bales with quality SIR 5, SIR 10, and SIR 20. The processing is done consists of several work stations that are continuous. Scheduling the work force in the company is considered less precise in providing holidays and working time, because hiring labor for 7 business days to achieve the production target and exceed 40 hours worked during the week. This is not in accordance with the Decree of the Minister of Manpower of the Republic of Indonesia No.102/MEN/IV/2004 and Law of the Republic of Indonesia No.13 of 2003 on Manpower. So it is necessary to apply a good scheduling system for labor production process, one of the laborscheduling algorithm is to use Monroe. The manpower requirements for the entire production process is as many as 73 people. With the labor scheduling in PT.ABC still can work to meet production targets without disrupting weekday though individual workers get a day off two consecutive days alternately. Another advantage in labor scheduling algorithm Monroe with the company is able to minimize labor costs Rp.232.200.000/year.